2019
DOI: 10.1111/1467-9817.12291
|View full text |Cite
|
Sign up to set email alerts
|

Component skills that underpin listening comprehension and reading comprehension in learners with English as first and additional language

Abstract: Aims: The primary aim of this study is to augment our understanding of the component skills that underpin second-language learners' text comprehension by examining the direct and indirect roles of vocabulary knowledge and grammatical skills in second-language learners' listening and reading comprehension. Methods: Our sample included 134 learners with English as an additional language (EAL) and 74 with English as first language (EL1) (M age = 123.76, SD = 5.02 months). Results: Our path analyses underscored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 45 publications
8
33
0
2
Order By: Relevance
“…These results relate to previous findings on second language vocabulary: second language learners have been reported to possess smaller vocabularies in their second language (e.g. Babayiğit & Shapiro, 2020; Verhoeven, 2000) with fewer associative links between these words (e.g. Vermeer, 2001; see also the meta-analysis by Melby-Lervåg & Lervåg, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results relate to previous findings on second language vocabulary: second language learners have been reported to possess smaller vocabularies in their second language (e.g. Babayiğit & Shapiro, 2020; Verhoeven, 2000) with fewer associative links between these words (e.g. Vermeer, 2001; see also the meta-analysis by Melby-Lervåg & Lervåg, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Vermeer, 2001; see also the meta-analysis by Melby-Lervåg & Lervåg, 2014). They also match findings that vocabulary outcomes of both first and second language learners influence comprehension outcomes (Babayiğit & Shapiro, 2020; Verhoeven & van Leeuwe, 2012). Although the findings on the role of vocabulary in listening comprehension sit well with models and empirical findings of comprehension, there are limits to the conclusions that can be drawn.…”
Section: Discussionsupporting
confidence: 80%
“…With EM students in elementary and secondary grades, Christopher et al (2012) found that after controlling for cognitive predictors, the correlation between latent D and LC factors dropped significantly (p < .01), from .59 to .28, supporting the prediction that cognitive skills underlie shared variance between D and LC. With EBs, a few studies have examined the roles of general cognitive predictors, such as working memory (Farnia & Geva, 2013) and nonverbal reasoning (Babayiğit & Shapiro, 2020), in addition to D and varied measures of LC, with mixed findings and not specifically addressing the shared variance between D and LC. Wu, Barquero, Pickren, Taboada Barber, and Cutting (2020) recently demonstrated that two of the three specific EF skills that we examined (cognitive flexibility and inhibition) not only predicted growth in reading comprehension in EMs from grade 1 to grade 4 but also that children with stronger EFs demonstrated faster rates of growth in reading comprehension.…”
Section: The Current Study: the Role Of Ef Skills In Explaining Shared Variance In D And Lcmentioning
confidence: 99%
“…With EM students in elementary and secondary grades, Christopher et al (2012) found that after controlling for cognitive predictors, the correlation between latent D and LC factors dropped significantly ( p < .01), from .59 to .28, supporting the prediction that cognitive skills underlie shared variance between D and LC. With EBs, a few studies have examined the roles of general cognitive predictors, such as working memory (Farnia & Geva, 2013) and nonverbal reasoning (Babayiğit & Shapiro, 2020), in addition to D and varied measures of LC, with mixed findings and not specifically addressing the shared variance between D and LC.…”
Section: The Current Study: the Role Of Ef Skills In Explaining Shared Variance In D And Lcmentioning
confidence: 99%
“…Although the cause of the observed bilingual vocabulary disadvantage is likely to be multifactorial and continues to be debated (Soto-Corominas et al, 2020), it is well-established that a smaller vocabulary size undermines effective reading comprehension. In fact, several studies reported a direct association between limited bilingual vocabulary size and bilingual disadvantage in reading comprehension (Babayiğit, 2015;Babayiğit & Shapiro, 2020).…”
Section: Bilingual Cognitive Effects and Reading Comprehensionmentioning
confidence: 99%